A Camp Style Staging: Javier Milei’s Campaign Tours (2023) - Cicowiez, Mariano (2026)
Introduction: The aesthetic occupation of public space was a recurring dimension in the campaign events carried out by the political party La Libertad Avanza in 2023. Objective: To examine the recording procedures of the campaign events as a subsidiary to the exhibition of staging that hides the intervention of the filming device. Methods: The corpus employed includes videos uploaded to the social media networks of the candidate Javier Milei under the name The Freedom Tour. An analysis of the composition resources included in the visual band of the videos was carried out. Results: It was found that the staging was designed to highlight a number of the presidential candidate’s personal traits. Conclusions: La Libertad Avanza resorted to composition procedures that belong to audiovisual aesthetics to position the candidacy of Javier Milei.